Основні принципи підготовки фахівців у сфері протидії кіберзлочинності - Марков, В. В.; Markov, V. V.; ORCID: http://orcid.org/0000-0003-2024-657X (Вісник Харківського національного університету внутрішніх справ. - 2015. - № 3 (70). - С. 223-234., 2015)
На прикладі досвіду функціонування моделі професійно-орієнтованого навчання, впровадженої на факультеті підготовки фахівців для підрозділів боротьби з кіберзлочинністю та торгівлею людьми Харківського національного університету внутрішніх справ, охарактеризовано основні організаційні та педагогічні принципи підготовки фахівців у сфері протидії кіберзлочинності, надано рекомендації щодо її подальшого сталого розвитку та вдосконалення.

The article highlights the problem of cybercrime counteraction in Ukraine and basic principles of training specialists in combating cybercrime. The author gives general characteristic of Kharkiv National University of Internal Affairs, the Faculty of Training Specialists in Combating Cybercrime and Human Trafficking and cybercrime combating and cyberspace monitoring training center that was established at the faculty on the voluntary basis. The significance of collaboration of the cybercrime combating and cyberspace monitoring training center with local cybercrime combating units of the Ministry of Internal Affairs of Ukraine as well as with international organizations is emphasized. The description of the basic principles of training specialists in combating cybercrime is provided: availability, methodicalness, complex and systematic character of training. Analyzing the present day situation in Ukraine the author draws a conclusion about the lack of well trained specialists in combating cybercrime in law enforcement agencies and gives recommendations for further improvement of training specialists in combating cybercrime.

На примере опыта функционирования модели профессионально-ориентированного обучения, внедрённой на факультете подготовки специалистов для подразделений по борьбе с киберпреступностью и торговлей людьми Харьковского национального университета внутренних дел, охарактеризованы основные организационные и педагогические принципы подготовки специалистов в сфере противодействия киберпреступности, даны рекомендации по её дальнейшему развитию и усовершенствованию.
Markov, V.V. (2015), “Basic principles of training specialists in combating cybercrime” [“Osnovni pryntsypy pidhotovky fakhivtsiv u sferi protydii kiberzlochynnosti”], Visnyk Kharkivskoho Natsionalnoho Universytetu Vnutrishnikh Sprav, No. 3, pp. 223-234.
Марков, В. В. Основні принципи підготовки фахівців у сфері протидії кіберзлочинності // Вісник Харківського національного університету внутрішніх справ. - 2015. - № 3 (70). - С. 223-234.
Марков В. В. "Основні принципи підготовки фахівців у сфері протидії кіберзлочинності." Вісник Харківського національного університету внутрішніх справ 3 (2015): 223-234.
Keywords: Адміністративне право та процес. Адміністративна діяльність. Administrative Law and Procedure. Administrative Activity. Административное право и процесс. Административная деятельность; Освіта. Педагогіка. Education. Pedagogy. Образование. Педагогика; Органи внутрішніх справ. Internal affairs agencies. Органы внутренних дел; Наукові публікації. Scientific publications. Научные публикации; кіберзлочинність; протидія кіберзлочинності; принципи професійної підготовки; випереджальне навчання; навчально-тренувальний центр боротьби з кіберзлочинністю та моніторингу кіберпростору; модель професійно-орієнтованого навчання; cybercrime; cybercrime counteraction; principles of professional training; passing ahead studies; cybercrime combating and cyberspace monitoring training center; model of the professionally-oriented studies; киберпреступность; противодействие киберпреступности; принципы профессиональной подготовки; опережающее обучение; учебно-тренировочный центр по борьбе с киберпреступностью и мониторинга киберпространства; модель профессионально-ориентированного обучения